Shakespeare in theory and practice - Belsey, Catherine (Edinburgh University Press, 2008)
In these essays, collected here for the first time, renowned critic Catherine Belsey puts theory to work in order to register Shakespeare's powers of seduction, together with his moment in history. Teasing out the meanings of the narrative poems, as well as some of the more familiar plays, she demonstrates the possibilities of an attention to textuality that also draws on the archive. A reading of the Sonnets, written specially for this book, analyses their intricate and ambivalent inscription of desire. Between them, these essays trace the progress of theory in the course of three decades, while a new introduction offers a narrative and analytical overview, from a participant's perspective, of some of its key implications. Written with verve and conviction, this book shows how texts can offer access to the dissonances of the past when theory finds an outcome in practice. Key Features One of the foremost literary critics of a generation writing on the central figure of English literature Provides an exemplary demonstration of poststructuralist theory at work Pays particular attention to desire as a theme and as a component of interpretation Provides close readings of the texts combining the historical and theoretical